1998
DOI: 10.1042/bj3290321
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of four new mammalian monocarboxylate transporter (MCT) homologues confirms the existence of a transporter family with an ancient past

Abstract: Measurement of monocarboxylate transport kinetics in a range of cell types has provided strong circumstantial evidence for a family of monocarboxylate transporters (MCTs). Two mammalian MCT isoforms (MCT1 and MCT2) and a chicken isoform (REMP or MCT3) have already been cloned, sequenced and expressed, and another MCT-like sequence (XPCT) has been identified. Here we report the identification of new human MCT homologues in the database of expression sequence tags and the cloning and sequencing of four new full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
322
8
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(347 citation statements)
references
References 47 publications
16
322
8
1
Order By: Relevance
“…Although MCTs are primarily localized at the plasma membrane, the transport proteins are not glycosylated post‐translationally 4. Instead, several members have been shown to depend on the association with a highly glycosylated ancillary protein for correct targeting and functional expression at the plasma membrane.…”
Section: Structure Of Mct Transportersmentioning
confidence: 99%
“…Although MCTs are primarily localized at the plasma membrane, the transport proteins are not glycosylated post‐translationally 4. Instead, several members have been shown to depend on the association with a highly glycosylated ancillary protein for correct targeting and functional expression at the plasma membrane.…”
Section: Structure Of Mct Transportersmentioning
confidence: 99%
“…The relative amounts of mRNA were estimated by scanning densitometry of the autoradiograms (Phoretix ID quantifier, Non-linear Dynamics). The cDNA probes were as follows: MCT1, 545 bp RT -PCR product from human colon (Ritzhaupt et al, 1998b); GLUT1, 2.4 kb BamHI fragment (cDNA kindly provided by S Baldwin, University of Leeds, UK); MCT2, 679 bp RT -PCR product corresponding to nucleotides 731 -1409 (Lin et al, 1998); MCT4, 590 bp RT -PCR product corresponding to nucleotides 174 -763 (Price et al, 1998); 18S rRNA cDNA was a gift from J Hesketh, University of Newcastle-upon-Tyne and a 1.4 kb restriction product was used as a probe.…”
Section: Northern Blottingmentioning
confidence: 99%
“…In healthy human colon, MCT2 is not expressed, whilst low levels of MCT4 mRNA have been detected (Price et al, 1998). Functional properties of MCT2 and MCT4 as elucidated by expression in Xenopus oocytes have indicated that these MCT isoforms are able to transport a range of monocarboxylates (Halestrap and Price, 1999).…”
Section: Determination Of the Levels Of Mct2 And Mct4 Protein And Mrnmentioning
confidence: 99%
“…[8][9][10] In fact, there are known to be at least seven putative monocarboxylic acid transporter (MCT) isoforms. The mRNA representing five of the seven MCTs has been shown in human placenta 11 . Using brush border membrane preparations, a functional, proton-dependent MCT has been observed in tissues from rat 12,13 and human 14 placenta.…”
Section: Introductionmentioning
confidence: 99%